Discours « tenant lieu » d’un autre discours : un espace générique de la représentation de discours autre - Jacqueline Authier-Revuz (Corela, 2024)
When considering metalanguage activity, the fact of "reported discourse" is encompassed within the broader field of "representation of other discourse", in which the discourse in progress represents another discourse. While the relationship thus established is traditionally considered at the level of statements, through the realizations of the various modes of representation of the other discourse (direct discourse, indirect discourse, bivocal discourse, autonymic borrowing modalization, second assertion modalization), this article proposes to examine the articulation between a representing unit and a represented unit at the level of the text. It shows how the representation of the other discourse can appear as a primary defining criterion for a variety of discourse genres (summary, press review, pastiche...) thus brought together in a generic space. Finally, he sets out to delimit a specific zone within this space, bringing together genres in which the representing discourse has the property of substituting or "taking the place of" the represented discourse, provided it obeys social and institutional prescriptions, such as the genres of the "minutes" or the "report of meeting".